2017
DOI: 10.1002/jez.2069
|View full text |Cite
|
Sign up to set email alerts
|

Lag of Immunity Across Seasonal Acclimation States in Gopher Tortoises (Gopherus Polyphemus)

Abstract: Disease outbreaks are of increasing importance to ectothermic vertebrates as one of numerous results of global change. Anthropogenic climate change is predicted to increase climatic instability, thereby altering natural thermal environments. In this study, we evaluated the direct effects of rapid temperature change on immunity in Gopher Tortoises (Gopherus polyphemus). Specifically, we tested the lag hypothesis, which predicts significant misalignment of optimal and realized immunity when temperature rapidly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…This responsiveness is present in the unchanged BA in control S. odoratus subjected to different temperatures, and the temperature‐dependent increase in humoral immunity in LPS‐injected S. odoratus . Two different experiments have demonstrated a significant constraint in gopher tortoises: when freely thermoregulating tortoises reduced body temperature they also reduced immunity (Goessling et al, ) and when tortoises were exposed to a rapid temperature reduction, immunity was reduced after 48 hr (Goessling et al, ). In this study, S. odoratus rapidly compensated for the change in temperature to maintain stable immunity, whereas G. polymphemus in prior studies did not compensate for a change in temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This responsiveness is present in the unchanged BA in control S. odoratus subjected to different temperatures, and the temperature‐dependent increase in humoral immunity in LPS‐injected S. odoratus . Two different experiments have demonstrated a significant constraint in gopher tortoises: when freely thermoregulating tortoises reduced body temperature they also reduced immunity (Goessling et al, ) and when tortoises were exposed to a rapid temperature reduction, immunity was reduced after 48 hr (Goessling et al, ). In this study, S. odoratus rapidly compensated for the change in temperature to maintain stable immunity, whereas G. polymphemus in prior studies did not compensate for a change in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nexus between thermal physiology and immunology is a critical link to elucidate mechanisms by which organisms are constrained by and respond to environmental change ( sensu Raffel, Rohr, Kieseck, & Hudson, ). Recent evidence has shown that climate change, specifically climatic variability, can have significant negative effects on immunity in ectothermic vertebrates (Goessling, Guyer, & Mendonҫa, ; Raffel et al, ; Raffel, Halstead, McMahon, & Davis, ). Reptiles are ideal models for experimentally assessing how changes in environmental temperature affect population susceptibility to disease because of the direct relationship between thermal environments and reptile body temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…How the immune responses of different insects will react to changing environmental conditions remains an open question, as it is clear that one strategy does not fit all. Along these same lines, the paper by Goessling, Koler, Overman, Hiltbold, Guyer, and Mendonça () evaluated the direct effects of rapid temperature change on immunity in gopher tortoises and showed that during summer, but not winter, rapid temperature reduction caused a series of changes in immunity. Their findings demonstrate that rapid temperature changes constrain immunity in ectothermic vertebrates, which has implications for global climate change (Goessling et al., ).…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…Along these same lines, the paper by Goessling, Koler, Overman, Hiltbold, Guyer, and Mendonça () evaluated the direct effects of rapid temperature change on immunity in gopher tortoises and showed that during summer, but not winter, rapid temperature reduction caused a series of changes in immunity. Their findings demonstrate that rapid temperature changes constrain immunity in ectothermic vertebrates, which has implications for global climate change (Goessling et al., ). Two of the studies in this special issue fall into this final theme but are focused on species of conservation concern (golden eagles and polar bears) and illustrate the utility of ecoimmunological approaches in conservation.…”
Section: Theoretical Approachesmentioning
confidence: 99%
See 1 more Smart Citation